El Cerro de Alarcos (Ciudad Real) : formación y desarrollo de un oppidum ibérico : 20 años de excavaciones arqueológicas en el Sector III - García Huerta, Rosario, (Archaeopress Archaeology, 2020)
This title presents results from the archaeological research which has been carried out since 1997 in Sector III of the Alarcos site, located a few kilometres from Ciudad Real. The research has made it possible to understand the communities that, from the end of the Bronze Age to the end of the Iron Age, inhabited this town and its surrounding area.